2020
DOI: 10.1126/sciadv.abe0894
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the asymmetric human γ-tubulin ring complex by RUVBL1-RUVBL2 AAA ATPase

Abstract: The microtubule nucleator γ-tubulin ring complex (γTuRC) is essential for the function of microtubule organizing centers such as the centrosome. Since its discovery over two decades ago, γTuRC has evaded in vitro reconstitution and thus detailed structure-function studies. Here, we show that a complex of RuvB-like protein 1 (RUVBL1) and RUVBL2 “RUVBL” controls assembly and composition of γTuRC in human cells. Likewise, RUVBL assembles γTuRC from a minimal set of core subunits in a heterologous coexpression sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 71 publications
6
59
1
Order By: Relevance
“…In the most extensive study, Zimmermann et al characterized the cryo-EM structure and assembly mechanism of the recombinant γ-TuRC and showed that the recombinant γ-TuRC recapitulates the structural organization of the native γ-TuRC isolated from frog extracts or human tissue culture cells. [60] Remarkably, even though Zimmermann et al did not co-express actin in their recombinant system, the purified γ-TuRC contained actin as part of the luminal bridge, indicating that insect cell actin can replace human actin in the recombinant human γ-TuRC. Moreover, the authors showed that co-expression of human GCP2, GCP3 and γ-tubulin together with both MZT1 and MZT2 allows assembly of a stable human γ-TuSC unit that had a tendency to selfinteract and form small γ-TuSC oligomers.…”
Section: Systems For Recombinant Expression Of the γ-Turcmentioning
confidence: 98%
See 3 more Smart Citations
“…In the most extensive study, Zimmermann et al characterized the cryo-EM structure and assembly mechanism of the recombinant γ-TuRC and showed that the recombinant γ-TuRC recapitulates the structural organization of the native γ-TuRC isolated from frog extracts or human tissue culture cells. [60] Remarkably, even though Zimmermann et al did not co-express actin in their recombinant system, the purified γ-TuRC contained actin as part of the luminal bridge, indicating that insect cell actin can replace human actin in the recombinant human γ-TuRC. Moreover, the authors showed that co-expression of human GCP2, GCP3 and γ-tubulin together with both MZT1 and MZT2 allows assembly of a stable human γ-TuSC unit that had a tendency to selfinteract and form small γ-TuSC oligomers.…”
Section: Systems For Recombinant Expression Of the γ-Turcmentioning
confidence: 98%
“…The central aspect of the study by Zimmermann et al is the discovery of the RUVBL1-RUVBL2 AAA+ ATPase (Figure 4A) as a cofactor for efficient assembly of the γ-TuRC, both for recombinant expression systems as well as native biogenesis of the γ-TuRC in mammalian cells. [60] The authors showed that RUVBL1-RUVBL2 associates with the human γ-TuSC in vitro and when co-expressed with recombinant γ-TuSC in insect cells. However, co-expression was not required for formation of stable γ-TuSC units, suggesting that the AAA+ ATPase is rather involved in follow-up steps of γ-TuRC assembly.…”
Section: The Ruvbl1-ruvbl2 Aaa+ Atpase Assists In γ-Turc Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent structural studies have shown that γ-TuRCs purified from the cytosol of HeLa cells and Xenopus eggs are in a semi-open conformation in which γ-tubulin molecules do not perfectly match the geometry of a 13-protofilament microtubule (Consolati et al, 2020;Liu et al, 2020;Wieczorek et al, 2020). This is also observed in recombinantly generated human γ-TuRCs (Zimmermann et al, 2020;Wieczorek et al, 2021;Würtz et al, 2021). A conformational change into a fully closed ring that matches microtubule geometry is expected to increase the nucleation capacity of the γ-TuRC.…”
Section: Introductionmentioning
confidence: 67%